Nanotechnology for the Detection and Therapy of Stroke. Issue 11 (1st April 2014) - Kyle, Stuart; Saha, Sikha
<x xml:space="preserve">Abstract</x> Over the years, nanotechnology has greatly developed, moving from careful design strategies and synthesis of novel nanostructures to producing them for specific medical and biological applications. The use of nanotechnology in diagnostics, drug delivery, and tissue engineering holds great promise for the treatment of stroke in the future. Nanoparticles are employed to monitor grafted cells upon implantation, or to enhance the imagery of the tissue, which is coupled with a noninvasive imaging modality such as magnetic resonance imaging, computed axial tomography or positron emission tomography scan. Contrast imaging agents used can range from iron oxide, perfluorocarbon, cerium oxide or platinum nanoparticles to quantum dots. The use of nanomaterial scaffolds for neuroregeneration is another area of nanomedicine, which involves the creation of an extracellular matrix mimic that not only serves as a structural support but promotes neuronal growth, inhibits glial differentiation, and controls hemostasis. Promisingly, carbon nanotubes can act as scaffolds for stem cell therapy and functionalizing these scaffolds may enhance their therapeutic potential for treatment of stroke. This Progress Report highlights the recent developments in nanotechnology for the detection and therapy of stroke. Recent advances in the use of nanomaterials as tissue engineering scaffolds for neuroregeneration will also be discussed.